The Effect of Seamless Learning on Learning Outcomes - Utami, Listia; Setyosari, Punaji; Kuswandi, Dedi; Praherdhiono, Henry (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
This research investigates the effect of seamless learning on learning outcomes (problem-solving and procedural) in Basic Physics courses. LMS-assisted seamless learning strategy with zoom-assisted seamless learning strategy through a quasi-experimental research design with 2x2 factorial. This research involved 73 students at Akba Technology University Makassar as research subjects. They are students in the Basic Physics course in the first semester of the 2022/2023 academic year. Students are divided into two groups. The experimental group consisted of 37 students who carried out the learning process using a seamless learning strategy assisted by LMS, while the control group consisted of 36 students who carried out the learning process using a seamless learning strategy assisted by Zoom. This research uses test instruments in the form of multiple-choice and essays. Data analysis used Multivariate Analysis of Variance (MANOVA). The research results show that, firstly, there is a significant difference in problem-solving learning outcomes between students taught using seamless learning assisted by LMS and seamless learning assisted by Zoom. Second, there is a significant difference in procedural learning outcomes between students taught using seamless learning assisted by LMS and seamless learning assisted by Zoom.